Enhancing English Language Proficiency: Strategies For Improving Student Skills - Budiman, Budiman; Ishak, Jaswadi Ishaka Putra; Rohani, Rohani; Lalu, Lalu Muh Halilurrahman; Jaelani, Slamet Riadi Jaelani, M.Pd (Kirana Publisher (KNPub), 2023)
English language proficiency is a critical skill for academic success, particularly for culturally and linguistically diverse students. This article aims to provide educators with effective strategies to assist these students in developing the literacy skills necessary for academic success. The problem is that English language learners (ELLs) have particular educational needs that require specialized teaching approaches. The purpose of this article is to provide educators with effective strategies to assist ELLs in developing literacy skills crucial for academic success. The Qualitative method used is a review of literature, including theories of language acquisition and learning, differences in social and academic language, and effective English language learning strategies employed by successful language learners. The participants of this study were Thirty Students in one of the senior high schools in Lombok Timur. The results of this review include six essential strategies for teaching ELLs, including cultivating relationships and being culturally responsive, teaching language skills across the curriculum, using real objects to illustrate concepts, role-playing or pantomiming, pointing to pictures, and employing total physical response.